A study on change in behavioral pattern with reference to the select novels of Amitav Ghosh - Dr.Sreela.B,Dr.SreejaBalakrishnan,K.PoornimaVaralakshmi, Yamini P, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article is an attempt to illustrate the different ways through which culture gets transformed as a result of contact with other cultures. The desire to gain sociability forms ground for cultural changes such as accultration, assimilation, diffusion and other types of cultural changes. Amitav Ghosh is a prolific writer who occupies an invincible space among the national and also the international writers. Six of his novels are analysed to study the changes in the behavioral patterns of the characters in the novel. Cognition is a mighty factor that conditions the thoughts of every human. The desire to garner solidarity and establish sociability is the chief reason for cultural compromises. Therefore, Georg Simmel’s theory on sociabilities is taken into account to support this study.